Combined Anterior Cruciate Ligament Reconstruction and Lateral Extra-Articular Tenodesis: The "Over-the-Top" Technique - Stefano Zaffagnini MD; Alberto Grassi MD; Gian Andrea Lucidi MD; Giacomo Dal Fabbro MD; Luca Ambrosini MD (SAGE Publishing, 2023)
Background: The anterior cruciate ligament (ACL) is a primary restraint to anteroposterior as well as rotatory knee laxity. In case of concomitant lesion of menisci or other ligamentous structures, further dynamic instability is encountered. A lateral extra-articular tenodesis (LET) augmentation has been proposed by the Authors to treat or prevent residual laxity. Indications: ACL reconstruction is recommended in young athletes involved in pivoting sports, non-contact pivoting injuries, high-grade pivot shift, deep notch sign and double bone bruise, meniscal loss, and revision of previous bone-patellar tendon-bone autograft. Technique Description: A 2 to 3 cm oblique incision is made over the pes anserinus. Gracilis and semitendinosus tendons are harvested with their attachment preserved and sutured together. Tibial tunnel is reamed after positioning of a guide pin. A wire-loop passer is directed from the tibial tunnel to the anteromedial portal. A 2 to 3 cm longitudinal incision is made superior-laterally, the ileotibial band is divided and retracted anteriorly. A suture-loop is retrieved from the lateral incision through the anteromedial portal with a curved Kelly clamp. The suture is placed into the wire-loop and retrieved with it from the tibial tunnel. The graft is retrieved from the lateral incision, tensioned with the knee at 70° to 90° of flexion and foot in neutral rotation and secured with 2 staples to the femur. A 1-cm skin incision is performed just below the Gerdy tubercle. The graft is retrieved from this incision below the fascia with a small Kelly clamp, tensioned and secured with a staple. The iliotibial tract defect is closed. Results: At long-term follow-up, a revision rate of 3% has been reported, while patient-reported outcome measures (PROMs) were excellent. At very-long-term follow-up, most patients were still involved in sports with a very low rate of positive Lachman and pivot shift tests. No overconstraint and lateral osteoarthritis were encountered. Medial osteoarthritis was related only to medial meniscectomy. Discussion/Conclusion: The ACL reconstruction plus LET over-the-top technique is a safe and reliable surgery with a low rate of reoperations and peri-operative complications at very-long-term follow-up. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.